DMAIC METHODOLOGY APPLIED IN THE TRAFFIC SECTOR OF AN URBAN SOLID WASTE COLLECTION COMPANY - Alberto Soares Santos; Pedro Vieira Souza Santos; Ciro Henrique de Araújo Fernandes; Ângelo Antônio Macedo Leite (Revista e-TECH: Tecnologias para Competitividade Industrial - ISSN - 1983-1838, 2025)
This work proposed the adapted application of the DMAIC methodology with the objective of improving the efficiency of the urban solid waste collection process in a company in Juazeiro, Bahia, identifying root causes of the problem and suggesting practical solutions. First, the “Define” stage involved the construction of a SIPOC (Suppliers, Inputs, Process, Outputs, Customers) to identify the problematic parts of the collection process. Through dialogues and discussions, the scope, objectives and goals of the project are clearly established. In the “Measure” stage, historical data were collected and compiled from April to October 2024 to evaluate the performance of the operation, using the Daily Collection Control (CDC) and an integrated spreadsheet (Global Spreadsheet), which records schedules, sectors, teams and vehicle performance. In the “Analyze” stage, the study applied tools such as the Ishikawa diagram to identify and prioritize the main causes that impact average travel time, carried out through brainstorming sessions with employees directly involved in the process, such as collectors, drivers and managers.